Mengembangkan Karakter Wirausaha Kelompok Wanita Tani melalui Penerapan Living Values Education di Usaha Peningkatan Pendapatan Keluarga (UP2K) Sukamaju, Desa Ajaobaki, Kecamatan Mollo Utara, Kabupaten Timor Tengah Selatan - Fransiskus Markus Pereto Keraf; Nurlailah Nurlailah; Fredik Lambertus Kollo (Fakultas Pertanian, Universitas Timor, 2023)
This research is motivated by the low interest in entrepreneurship of members of the Sukamaju women's farmer group. The purpose of this study was to determine the process of developing the entrepreneurial character of members of the Sukamaju farmer women's group through the application of living values education. The research process uses a qualitative approach with a descriptive method. The subjects in this study were group leaders, members and the surrounding community. Data collection techniques used are observation, interviews, and documentation. Analysis of the validity of the data consists of data reduction, presentation, and drawing conclusions. The method used by farmer women's groups in developing entrepreneurial character is through the application of living values education, appreciation, cooperation and responsibility. The results showed that through the application of living values education carried out by the Sukamaju farmer women's group, they were able to strengthen the entrepreneurial character of their group members. This is evidenced by the behavior and daily activities of the members of the women's farmer group who show entrepreneurial character.